Test-Retest Reliability of the Isometric Soleus Strength Test in Elite Male Academy Footballers - David Rhodes; Josh Jeffery; Daniel Brook-Sutton; Jill Alexander (North American Sports Medicine Institute, 2022)
# BACKGROUND Currently there is no reliability data available for the isometric soleus strength test (ISST), commonly used as a monitoring tool in elite football settings. Isometric strength testing for other muscle groups, most notably the hamstrings, is utilized to identify injury risk and readiness to train/play. To profile athletes efficiently, performance practitioners require optimal measures that are reliable. The aim of this study was to investigate the test-retest reliability of the isometric strength test of the soleus and propose a standardized protocol for its use within an elite male football population. # STUDY DESIGN Test-retest reliability single cohort study. # METHODS Thirty elite male footballers (age = 22.8±5.0 years, height = 180.0±0.08 cm, weight = 70.57±4.0 kg) performed the ISST, through three maximum 3-second hold efforts with one minute rest between repetitions and 48 hours between tests, in each test. The test was performed mid-competitive season. All data bilaterally were checked for normality using the Shapiro-Wilk test before a Pearson's Correlations and Bland-Altman's analyses were performed. # RESULTS Test-retest reliability demonstrated high reliability for ISST bilaterally (Right: r = 0.89; Left: r = 0.79, *p*\<0.05). The standard error of measurement (SEM) (%) was 9.09 - 12.47% and minimal detectable change (MDC) was 25.19 -- 34.56 (N) for Peak Force (PF) measures of the ISST. Bilateral levels of agreement were found to be +/- 2 standard deviations (SD) of the interval of agreement bilaterally for ISST (Levels of agreement (LOA): Right: Upper 352.49 - Lower -494.76; Left: Upper 523.82 - Lower -591.30. Bilaterally no significant difference was detected between values (Right: *p=0.09, CI: -153.21-10.95*; Left: *p=0.52, CI: -139.81-72.33*). # CONCLUSION The results of this study demonstrate high reliability for the ISST. The ISST displays a high test-retest reliability for assessing PF characteristics of the soleus in elite male academy footballers. This test may be beneficial for performance practitioners for profiling soleus function of athletes.